Stratosphere and lower mesosphere wind observation and gravity wave activities of the wind field in China using a mobile Rayleigh Doppler lidar. Issue 8 (10th August 2017) - Zhao, Ruocan; Dou, Xiankang; Xue, Xianghui; Sun, Dongsong; Han, Yuli; Chen, Chong; Zheng, Jun; Li, Zimu; Zhou, Anran; Han, Yan; Wang, Guocheng; Chen, Tingdi
Abstract: Since the mobile Rayleigh Doppler lidar of the University of Science and Technology of China was developed in 2013, more than 100 days of valid nighttime wind data from 15 to 60 km altitude were obtained during recent 3 years. The observation locations cover the northwest (midlatitude) of China: Delingha (37.371°N, 97.374°E), Xinzhou (38.425°N, 112.729°E), and Jiuquan (39.741°N, 98.495°E). Recently, we have extracted perturbations of the wind profiles from the wind field measurements and we have found that inertia gravity waves and mountain waves existed at the same time. The results of wind field and several gravity waves cases are shown in this paper. Typical characteristics of the gravity waves are analyzed in this midlatitude area of China. A 2‐D fast Fourier transform of the wind perturbation shows that a dominant stationary wave mode and a downward wave mode exist simultaneously in the spectrum. A band‐pass 2‐D filter was applied to the spectrum followed by inverse fast Fourier transform to separate inertia gravity waves from stationary mountain waves. The horizontal wavelength is retrieved using hodograph methods, indicating that the inertia waves are generated thousands of kilometers away. Observed mountain waves from a combination of vertical wind and leaned line of sight wind measurements show a small‐angle leaned wave front from the horizontal direction. This kind of gravity wave observation of the stratospheric wind field and its wave patterns is rare and significant for the study of atmospheric dynamics. Plain Language Summary: Stratosphere inertia and mountain gravity waves of wind field in northwest of China were observed by a Rayleigh Doppler wind lidar. The perturbation of the wind data shows dominant downward waves from 15 to 50 km altitude, and stationary mountain wave propagated up to 35 km. The 2‐D filter is applied to the perturbation to isolate the dominant single mode. The inertia wave has a typical vertical wavelength of 7 km, horizontal wavelength of 1300 km, and intrinsic period of 13 h, which are calculated by hodograph method. The mountain wave shows a wavefront with a small leaned angle from horizontal and vertical wavelengths of 6.7 km. This is the first time of observing mountain waves and inertia waves at the same time from altitude 15 km to 50 km by a Rayleigh Doppler lidar system. Key Points: Inertia gravity waves and mountain waves of the wind field in the stratosphere were observed by Rayleigh Doppler lidar The 2‐D filtered perturbations indicate typical inertia waves with about 7 km vertical wavelength, 1300 km horizontal wavelength, and 13 h intrinsic period Stationary mountain waves and downward inertia waves exist at the same time; 2‐D FFT is applied to separate inertia waves from the stationary waves